2020
DOI: 10.1002/eji.201948478
|View full text |Cite
|
Sign up to set email alerts
|

Manipulation of epithelial integrity and mucosal immunity by host and microbiota‐derived metabolites

Abstract: The human intestinal tract contains a large number of microbes, their metabolites, and potentially harmful food antigens. The intestinal epithelium separates the mucosa where immune cells are located from luminal microbes by expressing various factors that assemble into physical and chemical barriers. In addition to epithelial cells, immune cells are essential for enforcing mucosal barriers through production of inflammatory and anti-inflammatory mediators. Intestinal microbiota, represented by gut ecological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(22 citation statements)
references
References 104 publications
1
18
0
3
Order By: Relevance
“…The difference in the gut microbiome is likely to be the major driving force behind therapeutic outcomes between oral and rectal deliveries of EGCG. Considering the modulation of epithelial integrity and mucosal immunity by the microbiota and microbiota-derived metabolites [58,59], and the correlation we have revealed here, we concluded that the gut microbiome induced by EGCG contributes to the homeostatic balance of colon. This conclusion is further supported by the fact that EGCG has a low bioavailability and is poorly absorbed by the GI tract and thus its direct impact on host physiology is believed to be rather limited [21].…”
Section: Discussionsupporting
confidence: 56%
“…The difference in the gut microbiome is likely to be the major driving force behind therapeutic outcomes between oral and rectal deliveries of EGCG. Considering the modulation of epithelial integrity and mucosal immunity by the microbiota and microbiota-derived metabolites [58,59], and the correlation we have revealed here, we concluded that the gut microbiome induced by EGCG contributes to the homeostatic balance of colon. This conclusion is further supported by the fact that EGCG has a low bioavailability and is poorly absorbed by the GI tract and thus its direct impact on host physiology is believed to be rather limited [21].…”
Section: Discussionsupporting
confidence: 56%
“…Collectively, our results suggested that EGCG-mediated microbial community, especially the enrichment of Akkermansia played a key role in the alleviation of colitis, which could be the major driving force behind reversal outcomes between oral and rectal deliveries of EGCG. These increased populations of SCFAs-producing microbes and their metabolites induced by EGCG delivery might also be involved in maintaining the homeostatic balance in the colon by improving the colonic epithelial integrity and mucosal immunity [65,66]. These results are summarized in Fig.…”
Section: Discussionmentioning
confidence: 94%
“…including Kyn, XA and CA, are the ligands at the aryl hydrocarbon receptor (AHR), a transcription factor that regulates the maturation of different immune cells, epithelial renewal, and barrier integrity, thereby contributing to mucosal homeostasis 21,42,[46][47][48] . However, the mechanism of the regulation of Per1 and mosquitoes might present novel strategies for mosquito control.…”
Section: Discussionmentioning
confidence: 99%
“…Serotonin that functions as a neurohormone in mosquitoes modulates insulin-like peptides expression 13 , ion transportation 14 , feeding behavior 15 , salivation 16 and heart rate 17 . In mammalians, tryptophan and its metabolites are also key mediators that regulate immune responses and gut barrier function, thereby affecting hosts' susceptibility to pathogen infections [18][19][20][21][22][23] . However, little is known about the influence of mosquito tryptophan metabolism on pathogen transmission.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation